Perlindungan Hukum terhadap Anak yang Dilahirkan dari Perkawinan Siri dalam Poligami Tanpa Izin: Analisis Penetapan Pengadilan Agama Kudus Nomor 94/Pdt.P/2022/PA.Kds - Suhada Sholikhin; Deny Puspitasari (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Marriage is a legal institution that establishes civil relationships between spouses and their children. In Indonesia, a marriage is legally recognized when it complies with religious law and is officially registered. However, unregistered marriages (nikah siri) remain common and often create legal uncertainty, particularly regarding the civil status of children. This issue becomes more complex when the unregistered marriage is conducted by a man who is still legally married to another woman without obtaining court approval for polygamy. This study aims to analyze the legal consequences for children born from such marriages and to examine the legal reasoning of the judges in the Decision of the Kudus Religious Court Number 94/Pdt.P/2022/PA.Kds. This research employs a normative juridical method using statutory, case, and conceptual approaches. The findings show that children born from unregistered marriages remain biologically related to both parents but may face administrative obstacles in proving their civil relationship with the father. Nevertheless, Constitutional Court Decision Number 46/PUU-VIII/2010 allows such children to establish civil relations with their biological father through valid legal evidence. The determination of a child’s origin by the court provides legal certainty and ensures the fulfillment of rights to identity, maintenance, education, and inheritance. The judges in Decision Number 94/Pdt.P/2022/PA.Kds adopted a progressive approach by prioritizing the best interests of the child over the formal absence of marriage registration.